2020
DOI: 10.1093/europace/euaa311
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of low-voltage areas using modified APPLE score

Abstract: Aims The presence of low-voltage areas (LVAs) in patients with atrial fibrillation (AF) reflects left atrial (LA) electroanatomical substrate, which is essential for individualized AF management. However, echocardiographic anteroposterior LA diameter included into previous LVAs prediction scores does not mirror LA size accurately and impaired left ventricular ejection fraction (LV-EF) is not directly associated with atrial myopathy. Therefore, we aimed to compare a modified (m)APPLE score, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
2
14
0
3
Order By: Relevance
“…Increased oxidative stress and inflammation can lead to IR and impaired insulin secretion [ 24 ]. Inflammation, IR, and oxidative stress injury are linked to one another and, consequently, result in atrial electrical remodeling [ 18 , 24 ], LA fibrosis [ 18 ], and LA low-voltage areas(LVAs) [ 25 ], which are likely the main constituents of AF pathophysiology [ 25 , 26 ]. Most components of IR, such as glucose tolerance abnormalities, obesity and abnormal lipid levels, were found to have an additive effect on the risk of AF progression, which has been reported to be related to late recurrence of AF after RFCA [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased oxidative stress and inflammation can lead to IR and impaired insulin secretion [ 24 ]. Inflammation, IR, and oxidative stress injury are linked to one another and, consequently, result in atrial electrical remodeling [ 18 , 24 ], LA fibrosis [ 18 ], and LA low-voltage areas(LVAs) [ 25 ], which are likely the main constituents of AF pathophysiology [ 25 , 26 ]. Most components of IR, such as glucose tolerance abnormalities, obesity and abnormal lipid levels, were found to have an additive effect on the risk of AF progression, which has been reported to be related to late recurrence of AF after RFCA [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…APPLE and DR-FLASH scores were recently verified as predictors of LA fibrosis and LVAs, which are closely associated with AF progression and reflect the severity of the AF stage [ 9 , 11 ]. A recent study reported that APPLE and DR‐FLASH scores were associated with LA remodeling or fibrosis [ 9 , 11 , 25 ]. In the present study, we found that the elevated TyG index significantly increased as the APPLE, DR-FLASH and CHA 2 DS 2 -VASc scores increased.…”
Section: Discussionmentioning
confidence: 99%
“…Although late gadolinium-enhanced cardiac magnetic resonance imaging can detect LA fibrosis, and the extent of the late gadolinium enhancement area correlates with a high recurrence rate of AF after ablation [ 20 ], most hospitals would not be able to perform routine cardiac magnetic resonance imaging before the ablation. Age, sex, and LA volume are the components of assessment tools, such as APPLE, modified APPLE, and DR-FLASH scores, which reportedly predict LVZs [ 18 , 21 , 22 ]. Our findings also revealed that age, female sex, and a larger LA volume were independent pre-procedural predictors for LVZs in line with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested an approximately 2-fold higher amount of LA fibrosis in women as compared to men, but it is unclear whether this finding is an independent gender-dependent effect or linked to other risk factors. Recently, the APPLE-score, which does not include female gender, has been suggested as a potential tool to predict LA fibrosis prior to catheter ablation of AF [ 3 ].…”
Section: Introductionmentioning
confidence: 99%